Perbandingan Efektivitas Antara Ekstrak Kulit dan Buah Delima Merah (Punica granatum Linn) Terhadap Penyembuhan Kandidiasis Oral Tikus Wistar - Sri Hernawati; Ayu Mashartini Prihanti; Leni Rokhma Dewi; Refina Dikta Eryananda (Fakultas Kedokteran Gigi Universitas Jember, 2023)
Oral candidiasis is a fungal infection that occurs in the oral mucosa caused by the growth of Candida albicans. One of the antifungal drugs that are widely used by the public is nystatin. Nystatin is an effective drug because of its low toxicity level, but can cause side effects such as nausea, vomiting, diarrhoea, stomach pain, and resistance. In order to minimize these side effects, natural ingredients from red pomegranate can be used which have antifungal active ingredients in it. To compare the effectiveness of the whole extract with the skin of the red pomegranate (Punica granatum Linn) on the healing of oral candidiasis in Wistar rats. This research is a laboratory experimental study with a post-test only control group design. The samples used were 24 male wistar rats which were divided into 4 groups, namely (P1) the red pomegranate extract group with a concentration of 75%, (P2) the red pomegranate peel extract group with a concentration of 75%, (K+) the nystatin group, and (K -) the group that was not given anything. Microbiological examination and clinical examination (supporting examination). The data were analyzed using the Kruskal-Wallis non-parametric analysis test, the data before the extract and control showed no significant difference between each group (p>0.05) and the data after the extract and control administration showed there was a significant difference between each group. (p<0.05). Based on the Mann-Whitney test showed that red pomegranate extract and red pomegranate peel extract had a significant difference (p<0.05). Red pomegranate extract (Punica granatum Linn) at 75% concentration was more effective than red pomegranate skin extract (Punica granatum Linn) at 75% concentration on oral candidiasis treatment in wistar rats.